2021
DOI: 10.3390/cancers13143454
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Nanostructures for Nucleic Acid Delivery in Cancer: Current Trend, Emerging Issues, and Possible Solutions

Abstract: Cancer is one of the major health problems worldwide, and hence, suitable therapies with enhanced efficacy and reduced side effects are desired. Gene therapy, involving plasmids, small interfering RNAs, and antisense oligonucleotides have been showing promising potential in cancer therapy. In recent years, the preparation of various carriers for nucleic acid delivery to the tumor sites is gaining attention since intracellular and extracellular barriers impart major challenges in the delivery of naked nucleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 104 publications
0
19
0
Order By: Relevance
“…The precise delivery of UCNPs-Cas9 into hepatocytes was obtained by using the principle of immune escape and the homotypic targeting potential of CMs [ 53 ]. Generally, bio-inspired nanomaterials, such as albumin-based nanoparticles, do not show an adverse interaction with serum and enable the safe and efficient release of cargo into the cell cytoplasm [ 54 ]. Our findings showed that, BSA-PEI NPs can also be a promising carrier to deliver CRISPR/Cas9 into other types of cells for gene editing in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The precise delivery of UCNPs-Cas9 into hepatocytes was obtained by using the principle of immune escape and the homotypic targeting potential of CMs [ 53 ]. Generally, bio-inspired nanomaterials, such as albumin-based nanoparticles, do not show an adverse interaction with serum and enable the safe and efficient release of cargo into the cell cytoplasm [ 54 ]. Our findings showed that, BSA-PEI NPs can also be a promising carrier to deliver CRISPR/Cas9 into other types of cells for gene editing in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Several drugs and therapeutic NAs (TNAs) can be encapsulated into SA-based nanocarriers via electrostatic and hydrophobic interactions, as well as covalent conjugation. 82,106,121,127,135,138,144 Here, new perspectives into SA plasmatic functions and therapeutic applications are provided, highlighting the molecular aspects of SA:NAs recognition and the potential biotechnological implications of SA-based TNA delivery.…”
Section: Human Serum Albuminmentioning
confidence: 99%
“…The most commonly used albumins include egg-white (called ovalbumin), bovine serum albumin (BSA) and human serum albumin (HSA) (Figure 1) [43][44][45][46]. Among them, BSA is widely accepted and applied in research because of its low cost, and easy availability and purification [47]. However, milk, soy and legumes, among others, provide a new class of albumin base, recently providing the possibility for so-called green preparation [48].…”
Section: Source Of Albuminmentioning
confidence: 99%
“…Similar experiments may shed a light on the design of functional NPs and the influence of geometrical traits of cells such as cell spreading area and cell shape on the uptake of NPs. [30,47] There is some basic, technical scientific research aspects that should be handled prior to moving forward to the next step. For instance, the effects of synthesis conditions (such as particles size and stability and special properties of SANPs) on the applicability of NPs in general should be regarded.…”
Section: Future Perspective Of Albumin Nanoparticlesmentioning
confidence: 99%